2006
DOI: 10.1021/nl052361o
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Photonic Crystals Based on Solution-Processible Gold Nanoparticles

Abstract: We demonstrate the fabrication of metallic photonic crystals, in the form of a periodic array of gold nanowires on a waveguide, by spin-coating a colloidal gold suspension onto a photoresist mask and subsequent annealing. The photoresist mask with a period below 500 nm is manufactured by interference lithography on an indium tin oxide (ITO) glass substrate, where the ITO layer has a thickness around 210 nm and acts as the waveguide. The width of the nanowires can be controlled from 100 to 300 nm by changing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 17 publications
2
99
0
Order By: Relevance
“…The light was polarized parallel and perpendicular to the gold nanowires for TE and TM polarizations, respectively. As has been investigated extensively, waveguide resonance mode will be observed for TE polarization, which exhibits narrow-band peak features in optical extinction spectra [1,15]. However, Fano coupling between plasmonic and waveguide resonance modes can be observed for TM polarization, as shown in Figure 1c, where enhanced transmission or narrow-band dips in the optical extinction spectrum can be observed.…”
Section: Fabrication and Characterization Of The Plasmonic Gold Nanowmentioning
confidence: 95%
See 1 more Smart Citation
“…The light was polarized parallel and perpendicular to the gold nanowires for TE and TM polarizations, respectively. As has been investigated extensively, waveguide resonance mode will be observed for TE polarization, which exhibits narrow-band peak features in optical extinction spectra [1,15]. However, Fano coupling between plasmonic and waveguide resonance modes can be observed for TM polarization, as shown in Figure 1c, where enhanced transmission or narrow-band dips in the optical extinction spectrum can be observed.…”
Section: Fabrication and Characterization Of The Plasmonic Gold Nanowmentioning
confidence: 95%
“…The PR grating with a period of about 410 nm was fabricated on glass substrate with a 200-nm layer of indium tin oxide (ITO), where the ITO layer also acts as a waveguide. Chemically synthesized gold nanoparticles [15,16] with a diameter ranging from 5 to 10 nm, which were suspended in xylene with a concentration of 100 mg/mL, were then spin-coated onto the top surface of the grating. In the spin-coating process, a 30-μL colloidal solution of gold was spin-coated at a speed of 2000 rpm.…”
Section: Fabrication and Characterization Of The Plasmonic Gold Nanowmentioning
confidence: 99%
“…However, a small dynamic range of the fabrication area (<200 µm), low speed, and high costs are the obvious disadvantages of this method. The solution-processible fabrication [10][11][12] using colloidal gold nanoparticles has evolved into an important technique for the fabrication of both periodic and randomly distributed nanostructures, which supplies advantages like simplicity, large-area fabrication, and flexible tunability in spectroscopic response of the finished structures. However, this method generally produces structures in nanoscale, which is mainly limited by the size of the structures in the template, the required high concentration of the colloidal solution, and the annealing process of the gold nanoparticles in the size ranging from 5 to 10 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant previous studies have attempted to selectively infiltrate metal nanoparticles directly into nanopattern holes 23,24 or have used a template stripping method. [25][26][27][28] For example, the embedding of gold (Au) nanowires into an indium tin oxide anode layer was achieved by spin coating and surface energy-driven confinement of Au nanoparticles into the grating grooves.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] For example, the embedding of gold (Au) nanowires into an indium tin oxide anode layer was achieved by spin coating and surface energy-driven confinement of Au nanoparticles into the grating grooves. 23 In this case, strong coupling between the waveguide mode and the plasmon resonance nanowire in the transverse magnetic field mode could enhance direct-current conductivity and conferred unique optical behaviors. Furthermore, the template stripping method, initially developed by Frey et al, 25,26 has been shown to generate the same level of surface roughness of the embedded metal nanopattern surface as the surface of the target template for metal deposition.…”
Section: Introductionmentioning
confidence: 99%